(untitled) (PKP Barcelona 2019 Workshop, 2019)
Visit our demo site https://pkp.sfu.ca/ojs/ojs_demo/ Try the test drive site (username: admin; password: testdrive) Look at demos of different OJS themes Take PKP School free online courses and training videos https://pkpschool.sfu.ca/ Register for a free account to take the courses Review our documentation and user guides PKP Documentation Hub: https://docs.pkp.sfu.ca/index.html Learning OJS 3: https://docs.pkp.sfu.ca/learning-ojs/en/